The audacity of hope: thoughts on reclaiming the American dream - Obama, Barack (New York : Vintage Books, 2006)
Biography.
Includes index.
Keywords: African American legislators -- Biography; Obama, Barack -- Philosophy; United States-Congress-Senate -- Biography